2013
DOI: 10.1159/000355009
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Racial Differences on Body Composition and Total Body Water Measured by Multifrequency Bioelectrical Impedance Analysis Influence Delivered Kt/V Dialysis Dosing

Abstract: Introduction: Haemodialysis dosing is traditionally based on urea clearance (Kt/V). Aiming for the same Kt/V target, some racial groups have better survival. We investigated whether body composition differs with ethnicity and may lead to differences in Kt/V delivered. Methods: We compared total body water (TBW) measured by multifrequency bioelectrical impedance analysis (MF-BIA) that calculated from standard anthropometric equations. Results: Three hundred and seventy-one adult patients, with a mean age of 58.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
2
24
1
Order By: Relevance
“…Previous studies on BIS have reported on Caucasoid and African-American HD patients [2,3,22], and we did have patients from other ethnic groups, and reports have suggested that some bioimpedance measurements may vary between ethnic groups, but not in terms of ECW status [23,24], and we also did not find any association with ethnicity.…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies on BIS have reported on Caucasoid and African-American HD patients [2,3,22], and we did have patients from other ethnic groups, and reports have suggested that some bioimpedance measurements may vary between ethnic groups, but not in terms of ECW status [23,24], and we also did not find any association with ethnicity.…”
Section: Discussionmentioning
confidence: 47%
“…Of the two commonly used measures of dialyser urea clearance, the UK Renal Registry (UKRR) has historically reported the urea reduction ratio (URR), the percentage fall in serum urea following a mid-week dialysis session. Whilst the alternative Kt/V is a better method for measuring dialysis dose because it takes account of the size of a patient and urea removal by ultrafiltration, it requires data items not routinely collected by all UK renal centres [5][6]. URR is the most commonly used measure of urea clearance in dialysis centres in Europe in daily practice [7] and predicts minimum dialysis dose in the majority of patients consistently with Kt/V [8].…”
Section: Introductionmentioning
confidence: 99%
“…URR does not consider ultrafiltration or the size of the patient, and although Kt/V urea takes both into account, both URR and Kt/V urea can over-estimate dialyser urea clearance due to the rebound in serum urea concentration at the end of dialysis, particularly when higher blood pump speeds are used, and if blood sampling does follow approved protocols [2]. Whilst Kt/V provides a better estimate of urea clearance, it requires additional data items not routinely reported by most UK kidney dialysis centres [3,4]. As such, the UK Renal Registry (UKRR) has historically presented analyses based on URR rather than Kt/V urea for comparative audit of haemodialysis adequacy as these data are more readily available.…”
Section: Introductionmentioning
confidence: 99%